Chromosome-scale genome assembly provides insights into the evolution and flavor synthesis of passion fruit (Passiflora edulis Sims). (8th January 2021) - Xia, Zhiqiang; Huang, Dongmei; Zhang, Shengkui; Wang, Wenquan; Ma, Funing; Wu, Bin; Xu, Yi; Xu, Bingqiang; Chen, Di; Zou, Meiling; Xu, Huanyu; Zhou, Xincheng; et al.
Abstract: Passion fruit ( Passiflora edulis Sims) is an economically valuable fruit that is cultivated in tropical and subtropical regions of the world. Here, we report an ~1341.7 Mb chromosome-scale genome assembly of passion fruit, with 98.91% (~1327.18 Mb) of the assembly assigned to nine pseudochromosomes. The genome includes 23, 171 protein-coding genes, and most of the assembled sequences are repetitive sequences, with long-terminal repeats (LTRs) being the most abundant. Phylogenetic analysis revealed that passion fruit diverged after Brassicaceae and before Euphorbiaceae. Ks analysis showed that two whole-genome duplication events occurred in passion fruit at 65 MYA and 12 MYA, which may have contributed to its large genome size. An integrated analysis of genomic, transcriptomic, and metabolomic data showed that 'alpha-linolenic acid metabolism', 'metabolic pathways', and 'secondary metabolic pathways' were the main pathways involved in the synthesis of important volatile organic compounds (VOCs) in passion fruit, and this analysis identified some candidate genes, including GDP-fucose Transporter 1-like, Tetratricopeptide repeat protein 33, protein NETWORKED 4B isoform X1, and Golgin Subfamily A member 6-like protein 22 . In addition, we identified 13 important gene families in fatty acid pathways and eight important gene families in terpene pathways. Gene family analysis showed that the ACX, ADH, ALDH, and HPL gene families, especially ACX13/14/15/20, ADH13/26/33, ALDH1/4/21, and HPL4/6, were the key genes for ester synthesis, while the TPS gene family, especially PeTPS2/3/4/24, was the key gene family for terpene synthesis. This work provides insights into genome evolution and flavor trait biology and offers valuable resources for the improved cultivation of passion fruit.